The poverty elasticity of growth - Rasmus Heltberg (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
How much does economic growth contribute to poverty reduction? I discuss analytical and empirical approches to assess the poverty elasticity of growth, and emphasize that the relationship between growth and poverty change is non-constant. For a given poverty measure, it depends on initial inequality and on the location of the poverty line relative to mean income. In most cases, growth is more important for poverty reduction than changes in inequality, but this does not tender inequality unimportant. Reduction in inequality may be triple effective: (1) it will reduce poverty for a given level of income, (2) it will accelerate the poverty reducing impact of economic growth, and (3) according to crosscountry growth regressions, it may contribute to a larger rate of growth. – poverty ; poverty reduction ; economic growth ; inequality
Keywords: I31; O40; 330; Armut; Wirtschaftswachstum; Theorie